2017
DOI: 10.5551/jat.36426
|View full text |Cite
|
Sign up to set email alerts
|

Cardiothoracic Ratio as a Predictor of Cardiovascular Events in a Cohort of Hemodialysis Patients

Abstract: Aim: The cardiothoracic ratio (CTR) on a chest X-ray is an indicator of cardiac enlargement, although its predictive power for cardiovascular disease (CVD) events in chronic kidney disease is unknown. We examined it in a cohort of hemodialysis patients, as compared with an N-terminal fragment of probrain natriuretic peptide (NT-proBNP).Method: This was an observational study with cross-sectional and longitudinal analyses including 517 maintenance hemodialysis patients and 122 healthy control subjects. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Unlike NT -proBNP, CTR is not influenced by renal function 1) . CTR increases with cardiac hypertrophy, but it can also be influenced by other factors such as extracellular volume and pulmonary diseases such as pulmonary hypertension 11,12) . At the aforementioned four periods, the transition of this patient's CTR showed a temporary increase and decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike NT -proBNP, CTR is not influenced by renal function 1) . CTR increases with cardiac hypertrophy, but it can also be influenced by other factors such as extracellular volume and pulmonary diseases such as pulmonary hypertension 11,12) . At the aforementioned four periods, the transition of this patient's CTR showed a temporary increase and decrease.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no reports on the natural course of ICCAVB accompanied by serial changes of plasma NT -proBNP. We present a female preterm infant with ICCAVB in whom changes of plasma NT -proBNP were measured serially along with the cardiothoracic ratio (CTR) soon after birth 11,12) . This is the first report on combined use of CTR and NT -proBNP in the followup of ICCAVB.…”
Section: Introductionmentioning
confidence: 99%
“…As described elsewhere, 12,28,29 we defined CVD events in the DREAM cohort as the composite of the events related to ischemic heart disease, ischemic stroke, hemorrhagic stroke, peripheral artery disease, congestive heart failure, and cardiac valve disease. Ischemic heart disease events included myocardial infarction, percutaneous coronary intervention, and coronary artery bypass grafting.…”
Section: Definition Of Cvdmentioning
confidence: 99%
“…The selection of participants of the DREAM cohort from the total dialysis patients of Inoue Hospital was previously shown. 12,28,29 Among the 518 total participants of the cohort, we excluded 1 patient because of missing PUFA measurement. The remaining 517 participants were included in this study.…”
Section: Flow Of the Hemodialysis Patientsmentioning
confidence: 99%
“…They showed that the cardiac diameter, but not the CTR, was significantly correlated with the left ventricular size, the well-known predictor of cardiovascular morbidity and mortality. However, there are several studies that emphasize the utility of CTR in different entities [27][28][29][30][31]. Even CTR values that are within normal limits were found to have clinical implication.…”
Section: Editorialmentioning
confidence: 99%